Professional financial computing using Excel and VBA - Tung, Humphrey K. K.; Lai, Donny C. F; Wong, Michael C. S. [ (Michael Chak Sham)] (Singapore ; Hoboken, New Jersey : John Wiley & Sons, 2010)
Often financial computing guidebooks provide only quick-and-dirty implementations of financial models, rarely related to real-world applications. Professional Financial Computing Using Excel and VBA provides reusable, flexible, real-world implementations of financial models
1. Financial engineering and computing -- 2. The GARCH(1,1) model -- 3. Finite difference methods -- 4. Portfolio mean-variance optimization -- 5. Newton-Raphson method -- 6. Yield curve construction using cubic spline -- 7. Binomial option pricing model -- 8. The black-derman-toy model -- 9. Monte Carlo option pricing -- 10. Portfolio value-at-risk -- 11. The hull-white model -- 12. Credit Metrics model -- 13. KMV-Merton model
Series statement from jacket
Includes bibliographical references and index
Keywords: Microsoft Excel (Computer file); Microsoft Visual Basic for applications; Finance -- Data processing